Análisis de las relaciones de los procesos logísticos de un grupo de micro, peque\~nas y medianas empresas manufactureras colombianas; Analysis of the relationships of the logistics processes of a group of micro, small and medium colombian manufacturing companies - Mateo Márquez Gutiérrez; Guillermo León Carmona González; Carlos Alberto Castro Zuluaga (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– The purpose of this article is to explore the relationship that exists between a group of important logistics processes of Colombian micro, small and medium-sized manufacturing companies (MSMEs). Through a reduced number of factors, the vision of the analyzes carried out on this type of companies is simplified both from practice and from literature. For this, a methodology based on multivariate statistical analysis is used. The use of element analysis allows to have a general and descriptive vision of the business logistics processes. The exploratory factor analysis, for its part, allows obtaining a set of factors that better explain the processes, while a confirmatory factor analysis allows corroborating the validity of these factors in a sample of MSMEs.The main findings consider four main factors that best represent and relate the logistics and logistics impact processes considered for MSMEs with a high level of statistical validity. This research considers a limited number of manufacturing companies and assumes that the processes that were taken into account represent the logistics of a company, according to the literature. Finally, the simplification, through statistical analysis, of the logistics problems of manufacturing MSMEs in emerging markets is presented as the main contribution of this article.
Keywords: C10; M10; 330; factor analysis; MSMEs; logistic macroprocesses; element analysis; logistic variable correlation